Variational cluster approximation and exact diagonalization for calculation of Hubbard models. (March 2019) - Lukyanov, Alexander; Neverov, Vyacheslav; Zhumagulov, Yaroslav; Krasavin, Andrey
Abstract: The numerical method was developed that combines the variational cluster approximation and the exact diagonalization techniques to solve Hubbard models of various dimensionality, number of orbitals, and lattice geometry. The developed method was tested on the one-band Hubbard model; antiferromagnetic ordering and the superconducting phase were observed, in accordance with known results obtained by other techniques. The method may be successfully used for studying properties of high-temperature superconductors.